Produção de imunoglobulina Y (IgY) anti-Haemonchus contortus e aplicação imunoterápica em Meriones unguiculatus - Gressler, Lucas Trevisan (2018)
In the last decade, among the medium-sized herds (poultry, swine, sheep), the one with the highest growth rate was sheep. For the sheep farming, gastrointestinal helminths can be considered one of the main barriers for breeding today. Among these, we highlight the haemoncosis, caused by the Haemonchus contortus species, a cosmopolitan parasite, highly pathogenic and prevalent. This disease, in addition to causing the death and delayed development of animals, reduces production, resulting in increased breeding costs. Due to the importance of the control of this parasitosis, the massive and indiscriminate use of antihelmintics promoted the selection of multiresistant nematodes and, consequently, the deficient action of the products commercially available. Thus, to research this topic is essential for the prevention and control of infections caused by H. contortus. In this context, this thesis was elaborated with the aim of evaluate different experimental protocols for the establishment of H. contortus infection of Meriones unguiculatus with and without immunosuppression (manuscript 1); to produce and characterize anti-H. contortus immunoglobulins Y (IgY) from third instar larvae (L3) (manuscript 2) and adult stages of this helminth (manuscript 3), and to evaluate the IgY immunotherapeutic activity anti-H. contortus in Meriones unguiculatus experimentally infected. We observed that is possible to establish gerbils’ infection by H. contortus, after immunosuppression with methylprednisolone compared to dexamethasone immunosuppression and immunocompetent animals. Chickens immunized with third-stage larvae and adults of H. contortus produced immunoglobulins anti-H. contortus displaying specificity and high avidity. Lastly, we verified that immunotherapy interfered in the establishment of H. contortus in experimentally infected gerbils.